PENGARUH KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KINERJA GURU PAMONG DI SANGGAR KEGIATAN BELAJAR (SKB) KABUPATEN KARAWANG - Enjang Sudarman (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
Research Objectives: To determine the effect of communication and leadership on the performance of tutor teachers in the Karawang District Learning Activities (SKB). Design / Method: using regression methods, to find the influence between the variables studied, namely; independent variables of communication (X1) and leadership (X2) on the dependent variable of the performance of the tutor teacher (Y). Subjects in this study were tutors as many as 36 people from the total sample. Primary data sources were taken using questionnaires / instruments: communication variables, leadership variables, and tutor teacher performance variables. Data analysis using inferential statistics with SPSS version: 22. Findings: there was a simultaneous significant influence between communication and leadership on the performance of the tutor teacher (F = 359.21, p 0.000). Implications: (1) communication skills in the learning process in the classroom to understand the state of students, appreciate various views, comfortable and healthy in discussion. (2) Communication in the learning process is suggested by using an assertive style that will be more effective in achieving learning objectives. (2) leadership in the learning process by classifying students based on low, middle and high intelligence levels to make the discussion process more effective. Originality: (1) indicators of communication: aggressive, manipulative, passive and assertive, (2) leadership indicators: working with adult, communication skills. collaboration team. knowledge of content and pedagogy. (3) civil service teacher performance indicators: program planning, implementation, quality control and reporting.